(3COhGQ GdeQCI ai EYdGfGJ GdJdjaRjhf GdYQHjI h GfYcGSgG Ydi UhQI GdPGJ dOjgG (B/ s - (3QjgGf LeGd SdjeGf TYdGfs; (3ShRGf jhSa Gdbdjfi (B: s ((3GdbGgQI (B: s (3QjgGf LeGd SdjeGf TYdGf (B: s, 2020)
(3JJecf GdeQCI ef JMbjb ZGjGJgG h GdbjGe HegGegG h hGLHGJgG ef NdGd JaGYdgG eY HjFJgG GdGLJeGYjI(B: (3h ef NdGd eTGQcJgG GdBNQjf ai JMSjf XQha OGaYI GdeYGT(B. (3h ef Cge GdeDKQGJ GdJi SGYOJ ai GdJGKjQ ai PGJ GdeQCI gi GdEYdGfGJ(B: (3abO JMhdJ GdEYdGfGJ Edi COGI ddJCKjQ Ydi GdeQCI oeTpqcdI dTNUjJgG h SdhcgG GdGLJeGYi(B: (3abO CUHMJ GdEYdGfGJ GdJdjaRjhfjI GdYQHjI PGJ CgejI HGdZI GdCKQ djS Ydi GdUYjO GdEYdGei aMSH(B: (3h EfeG Ydi LejY GdCfSGb GdGLJeGYjI h GdKbGajI h GdGbJUGOjI h GdSjGSjI(B. (3abO obpqOneJ GdeQCI ai GdEYdGf HUhQ h CfeGW eJYOOI JQGhMJ Hjf eSJhjGJ ef GdGjLGHjI h GdSdHjI(B: (3ade jYO GSJNOGe GdeQCI ai GdEYdGfGJ GdNGUI HGdedGHS Ch GdYWhQ GdfSGFjI aMSH, Hd fLO Cf EYdGfGJ GdeCchdGJ h GdeTQhHGJ h eNJda GdSjGQGJ h GdNOeGJ LYdJ ef GdeQCI YfUQG CSGSjG JJVefg GdQSGFd GdEYdGfjI GdNGUI HgG(B. (3h ef Ke GgJeJ GdHGMKI HOQGSI h eYGdLI COhGQ GdeQCI ai EYdGfGJ GdJdjaRjhf GdYQHjI h EfYcGSgG Ydi UhQI GdPGJ dOjgG(B.. (3HfGAG Ydi fXQjI GdZQS GdKbGai h fXQjI GdPGJ MjK GSJNOeJ GdHGMKI efgL GdeSM ai OQGSJgG(B: (3eSJNOeI GSJeGQI JMdjd eVehf HhUagG COGg ddHMK(B: (3dQUO GdEYdGfGJ GdJi JSJNOe ajgG GdeQCI ai GdaVGFjGJ GdYQHjI NdGd GdaJQI ef (B6/5/2019 (3Edi (B3/6/2019.: (3h GdeYQhVI HGdbfhGJ GdJdjaRjhfjI HGdGVGa Edi GSJeGQI GdejOGfjI GdJi JHWb Ydi (B(400 (3eHMhKI(B). (3h bO MbbJ GdHGMKI GdgOa GdCSGSi ef GdHMK YfOeG NodUJ GdfJGFL Edi eG jdi(B: (3JfhY GdEYdGfGJ GdJdjaRjhfjI GdYQHjI eMd GdOQGSI habkG dfhY GdefJL h Pdc Ydi aFJjf geG(B: (3GdSdY h GdNOeGJs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdOhd GdYQHjI (B- (3GdefXeI GdYQHjI ddJQHjI h GdKbGaI h GdYdhe (B- (3eYgO GdHMhK h GdOQGSGJ GdYQHjI HGdbGgQI (B- (3bSe HMhK h OQGSGJ GdEYdGe s
(3UOQ GjVG cbQU eOeLs